Rāingān kānwičhai kānl̄ưaktang samāchik Saphā Phūth̄æn Rātsad̨ōn, 17 Phrưtsačhikāyon 2539 (ʻĒkkasān singphim (Thailand. Krom Kānpokkhr̨ōng. K̨ōng Wichākān læ Ph̄ænngān) ;, 1996)
Study on general election, 1996 in Thailand, with objectives to find administrative orderliness and public participation.